Systems Engineering Principles and Hypotheses. Issue 1 (29th May 2019) - Watson, Michael D.
ABSTRACT: The INCOSE Systems Engineering Principles Action Team has put forth a set of principles and hypotheses to articulate the basic concepts that guide systems engineering. The team based this work on a review of various sources of systems postulates, principles, and hypotheses identified in literature. They focused on the multi‐year work of the NASA Systems Engineering Research Consortium looking at the work of Ludwig Boltzmann and his postulates on gas distributions as an early example of how to characterize the interactions of complex systems. The INCOSE Systems Engineering Principles Action Team review has distilled the earlier works to the 15 principles and three hypotheses stated in this article. The principles define the domain of systems engineering as well as the system aspects and system influences that are of concern to the systems engineer. The hypotheses contain some of the seeds of a holistic mathematical basis for systems engineering.